Determinação experimental dos limites de inflamabilidade do biocombustivel hydrotreated vegetable oil (hvo) - Andrade, José Carlos de (Universidade Estadual Paulista (UNESP), 2026)
O HVO representa uma solução promissora para a descarbonização do setor de transportes, mas sua adoção em larga escala, particularmente em países como o Brasil, requer um entendimento detalhado de suas propriedades de segurança, como limites de inflamabilidade. A ausência desses dados na FISPQ, decorre da falta de testes padronizados e da variabilidade em sua composição, o que pode subestimar os riscos de armazenamento, transporte e uso. Esta dissertação propõe uma aborda-gem inovadora através de ensaios experimentais (ASTM E681) para determinar os limites de inflamabilidade do HVO considerando matérias-primas locais (óleo de soja e gordura animal), integrando os resultados em proposta de atualização regulatória junto à ANP. O aparato experimental consiste em recipiente esférico de vidro de 20 L, validado para HVO com incerteza combinada de ±2,19%, operando na faixa de 130-180°C e 10-101 kPa definida pelas características de pressão de vapor e temperatura de autoignição (477 K). Os principais resultados estabeleceram que, a 101 kPa, o LII do HVO variou entre 0,63% e 0,77% vol., contrariando o uso dos dados do diesel como substitutos devido à composição parafínica do HVO e sua resposta distinta à pressão. A 10 kPa, o LII elevou-se para 0,77–2,15% vol., evidenciando forte depen-dência da pressão. Os modelos de Zabetakis e Glassman subestimaram o LII em 67–88%, sendo inadequados para o HVO em condições subatmosféricas. As conclusões estendem-se ao LSI, por tratar-se do mesmo combustível parafínico. O trabalho pre-enche lacuna científica e prática, contribuindo para segurança operacional e viabili-dade do HVO como combustível renovável no contexto brasileiro, alinhado à transi-ção energética global.

HVO represents a promising solution for the decarbonization of the transportation sec-tor, but its large-scale adoption, particularly in countries such as Brazil, requires a de-tailed understanding of its safety properties, such as flammability limits. The absence of these data in Safety Data Sheets (SDS), as noted in the literature, stems from the lack of standardized testing and the variability in its composition, which may lead to underestimation of storage, transportation, and usage risks. This dissertation propos-es an innovative approach through experimental tests (ASTM E681) to determine the flammability limits of HVO considering local feedstocks (soybean oil and animal fat), integrating the results into a proposed regulatory update to ANP (Brazilian National Agency of Petroleum, Natural Gas and Biofuels). The experimental apparatus con-sists of a 20 L spherical glass vessel, validated for HVO with a combined uncertainty of ±2.19%, operating in the temperature range of 130–180°C and pressure range of 10–101 kPa, defined by the vapor pressure characteristics and autoignition tempera-ture (477 K). The main results established that, at 101 kPa, the LFL of HVO ranged from 0.63% to 0.77% vol., contradicting the current practice of using diesel data as substitutes due to the paraffinic composition of HVO and its distinct pressure re-sponse. At 10 kPa, the LFL increased to 0.77–2.15% vol., evidencing a strong pres-sure dependence. The Zabetakis and Glassman models underestimated the experi-mental LFL by 67–88%, proving inadequate for HVO under subatmopheric conditions. The same conclusions extend to the UFL, as they are properties of the same paraffin-ic fuel. This work fills a scientific and practical gap, contributing to the operational safety and viability of HVO as a renewable fuel in the Brazilian context, aligned with the global energy transition.
Experimental determination of the flammability limits of the biofuel hydrotreated vegetable oil (HVO)
Keywords: Biocombustível; Óleos vegetais como combustível; Combustão; Green Diesel